(3JjLGf Gdedhcs - (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjSJMb GdMeO GdG gh GdPi Ndb BOe ef GdWjf s
(3BNQgG (B:s
(3ajbhd Cgd GdfGQ YfO Pdc CeI eMeO Udi Gddg Ydjg hSde bO QMehG hGdMeO ddg QH GdYGdejf Je GdcJGH HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B192s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs